Segmental aortic stiffness in patients with bicuspid aortic valve compared with first-degree relatives. Issue 2 (4th August 2018) - Goudot, Guillaume; Mirault, Tristan; Rossi, Aude; Zarka, Samuel; Albuisson, Juliette; Achouh, Paul; Pernot, Mathieu; Messas, Emmanuel
Abstract : Aims: To compare the stiffness index in patients with bicuspid aortic valve (BAV) with first-degree relatives at each segment of the thoracic ascending aorta and to compare segmental analysis of aortic stiffness in association with BAV morphotype and function. Methods: 219 patients with BAV and 148 first-degree relatives (without BAV) were consecutively included at a reference centre for BAV. Ultrasound assessment of aortic and carotid stiffness was based on the variation of the segmental arterial diameters during the cardiac cycle and on blood pressure. Results: Without adjustment, the ascending aorta of patients with BAV seemed stiffer at each segment compared with controls (stiffness index at the sinus of Valsalva: 17.0±10.9 vs 8.9±6.1, p<0.001; tubular aorta: 20.4±31.3 vs 12.7±4.8, p=0.04). However, after adjustment on aortic diameter and age, only the sinus of Valsalva remained stiffer (p<0.001), whereas the tubular aorta no longer differed (p=0.610). In patients with BAV, aortic diameters were not influenced by the valve morphotype, except for the arch, which was more dilated in the case of 1- Non coronary sinus-Right subtype of BAV : 36.1 vs 27.6 mm, p<0.001. Aortic regurgitation was associated with an increase in aortic diameters at the sinus of Valsalva (p<0.001) and the tubular aortic levels (p=0.04). Conclusion: Stiffness increase at the sinus of Valsalva level is independent of aortic dilatation in patients with BAV, contrary to the classic relationship between stiffness and dilatation found on the other segments. The relationship between stiffness and clinical impact needs to be assessed at each aortic segment.